2018
DOI: 10.29252/jfqhc.5.3.84
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Agents in Fresh Fruits and Vegetables Sold in Open Markets in Bauchi, Nigeria

Abstract: HIGHLIGHTS  Parasitic contaminations were found in 14.3% of fruit and 13.8% of vegetable samples.  Ascaris lumbricoides was the most common parasitic contaminant in both fruit and vegetable samples.  Fresh fruits and vegetables consumed in Bauchi, Nigeria are the major sources of parasitic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
3
14
1
Order By: Relevance
“…Ascaris lumbricoides (33.33%) was the most frequently detected parasite in this study. This is similar to Istifanus & Panda (2018) report of Ascaris lumbricoides being the most prevalent parasitic contamination in both vegetables and fruits in his study. Hassan et al, (2013) reported the least infestation in his study for lime fruit.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ascaris lumbricoides (33.33%) was the most frequently detected parasite in this study. This is similar to Istifanus & Panda (2018) report of Ascaris lumbricoides being the most prevalent parasitic contamination in both vegetables and fruits in his study. Hassan et al, (2013) reported the least infestation in his study for lime fruit.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study corroborate with those of Asghar et al, (2013), Dada andOlusola-Makinde (2015) and Wedajo and Kadire (2019) who also discovered the presence of both parasites and microbes in fruits and vegetables. Istifanus & Panda (2018) in their study in Bauchi State noted the contamination of vegetables and fresh fruits with various parasitic cysts and ova. Amawulu et al, (2019) confirmed the infestation of fruits (20%) sold in Yenagoa, Bayelsa State Capital, with parasites.…”
Section: Discussionmentioning
confidence: 98%
“…El Said Said (2012); Duedu et al . (2014) and Istifanus and Panda (2018) reported that leafy greens such as lettuce, cabbage and rocket were more susceptible to contamination compared to other vegetables with smooth surfaces, due to their curly leaves that may increase the attachment of parasites such as Cryptosporidium and Giardia . In addition, Amahmid et al .…”
Section: Literature Selection Criteriamentioning
confidence: 99%
“…The structure of vegetables was largely involved in the level of parasitic contamination. El Said Said (2012); Duedu et al (2014) and Istifanus and Panda (2018) reported that leafy greens such as lettuce, cabbage and rocket were more susceptible to contamination compared to other vegetables with smooth surfaces, due to their curly leaves that may increase the attachment of parasites such as Cryptosporidium and Giardia. In addition, Amahmid et al (1999) found that leafy greens such as coriander and mint were relatively more contaminated with Giardia compared to carrots and radish, which could be related to their dense foliage offering a large contamination surface.…”
Section: Vegetable Typesmentioning
confidence: 99%
“…Parasites were detected in 58 out of 252 (23.02%) freshly harvested vegetable samples collected from selected organic and conventional farms in Northern and Southern Luzon Provinces in the Philippines (Ordoñez et al, 2018). According to Istifanus and Panda (2018), 26 (14.3 %) out of 182 of four different types of fruits samples, and 82 (13.8 %) out of 594 of six different types of vegetable samples sold in open markets in Bauchi were contaminated with various parasitic ova and cysts. Amawulu et al (2019) reported that out of the 40 fruits examined in Yenagoa, Nigeria, 8 (20%) were infested with parasites.…”
Section: Introductionmentioning
confidence: 99%